AA/12-Lipoxygenase Signaling Contributes to Inhibitory Learning in Hermissenda Type B Photoreceptors - Walker, Tony L.; Campodonico, Joanna J.; Cavallo, Joel S.; Farley, Joseph (Frontiers in Behavioral Neuroscience, 2010)
Conditioned inhibition (CI) is a major category of associative learning that occurs when an organism learns that one stimulus predicts the absence of another. In addition to being important in its own right, CI is interesting because its occurrence implies that the organism has formed an association between stimuli that are non-coincident. In contrast to other categories of associative learning that are dependent upon temporal contiguity (pairings) of stimuli, the neurobiology of CI is virtually unexplored. We have previously described a simple form of CI learning in Hermissenda, whereby animals’ phototactic behavior is increased by repeated exposures to explicitly unpaired (EU) presentations of light and rotation. EU conditioning also produces characteristic reductions in the excitability and light response, and increases several somatic K+ currents in Type B photoreceptors. Type B photoreceptors are a major site of plasticity for classical conditioning in Hermissenda. Because arachidonic acid (AA) and/or its metabolites open diverse K+ channels in many cell types, we examined the potential contribution of AA to CI. Our results indicate that AA contributes to one of the major effects of EU-conditioning on Type B photoreceptors: decreases in light-evoked spike activity. We find that AA increases the transient (IA) somatic K+ current in Type B photoreceptors, further mimicking CI training. In addition, our results indicate that metabolism of AA by a 12-lipoxygenase enzyme is critical for these effects of AA, and further that 12-lipoxygenase metabolites are apparently generated during CI training.